2020
DOI: 10.1097/txd.0000000000001049
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Acting Antiviral Therapy in Liver Transplant Patients With Hepatocellular Carcinoma and Hepatitis C

Abstract: Background: Direct-acting antivirals (DAA) are highly effective for the treatment of hepatitis C (HCV), although there are limited data on the safety and efficacy of DAA therapy in hepatitis C-positive individuals awaiting liver transplantation for hepatocellular carcinoma (HCC). Methods: We conducted a retrospective cohort study of HCV-positive patients who underwent liver transplantation for HCC at 3 liver transplant centers across the United States from 2014 to 2017 with follow-up to July 2018. Transplant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…One multicenter study of 875 HCV-HCC recipients showed no association between DAA and HCC recurrence, while another study with 171 HCV-HCC recipients showed a trend of decreased HCC recurrence in patients receiving DAAs (hazard ratio, 0.38; P=0.07). 59,60 These studies had the limitation of a relatively short follow-up period; therefore, more studies are needed to confirm the relationship between DAAs and HCC recurrence. Conversely, as HBV is predominant in the East, the potential differences in the effects of HBV and HCV on recurrence after LT should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One multicenter study of 875 HCV-HCC recipients showed no association between DAA and HCC recurrence, while another study with 171 HCV-HCC recipients showed a trend of decreased HCC recurrence in patients receiving DAAs (hazard ratio, 0.38; P=0.07). 59,60 These studies had the limitation of a relatively short follow-up period; therefore, more studies are needed to confirm the relationship between DAAs and HCC recurrence. Conversely, as HBV is predominant in the East, the potential differences in the effects of HBV and HCV on recurrence after LT should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of DAAs on the reduction of HCC recurrence after LT remains controversial. One multicenter study of 875 HCV-HCC recipients showed no association between DAA and HCC recurrence, while another study with 171 HCV-HCC recipients showed a trend of decreased HCC recurrence in patients receiving DAAs (hazard ratio, 0.38; P =0.07) [ 59 , 60 ]. These studies had the limitation of a relatively short follow-up period; therefore, more studies are needed to confirm the relationship between DAAs and HCC recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Direct-acting antiviral (DAA) drugs for HCV dramatically improve outcomes for patients who undergo liver transplantation (LT) and for other patients with advanced liver disease. [1][2][3] DAAs and high-dimensional analytical techniques, such as single-cell mass cytometry (cytometry time of flight [CyTOF]), provide a unique opportunity to investigate the immune dysregulation that occurs during chronic HCV infection and to measure the ability of curative treatment for a chronic viral infection to restore immune function. Persistent abnormalities may yield insights into immunological imprinting, and they may also be clinically important, especially in patients who have undergone LT and patients with advanced liver disease who have an increased infection risk.…”
Section: Introductionmentioning
confidence: 99%
“…Direct-acting antiviral (DAA) drugs for HCV dramatically improve outcomes for patients who undergo liver transplantation (LT) and for other patients with advanced liver disease 1–3 . DAAs and high-dimensional analytical techniques, such as single-cell mass cytometry (cytometry time of flight [CyTOF]), provide a unique opportunity to investigate the immune dysregulation that occurs during chronic HCV infection and to measure the ability of curative treatment for a chronic viral infection to restore immune function.…”
Section: Introductionmentioning
confidence: 99%